BODIPY‐Based Antiaromatic Macrocycles: Facile Synthesis by Knoevenagel Condensation and Unusual Aggregation‐Enhanced Two‐Photon Absorption Properties1. Issue 9 (17th January 2018) - Chua, Ming Hui; Kim, Taeyeon; Lim, Zheng Long; Gopalakrishna, Tullimilli Y.; Ni, Yong; Xu, Jianwei; Kim, Dongho; Wu, Jishan
Abstract: Two stable boron dipyrromethene (BODIPY)‐based antiaromatic macrocycles, Mc‐Fur andMc‐Th, were synthesized through a one‐pot Knoevenagel condensation reaction between a BODIPY precursor and furan‐2, 5‐dicarboxaldehyde or thiophene‐2, 5‐dicarboxaldehyde, respectively. 1 H NMR spectroscopic characterization of the two macrocycles supported their highly antiaromatic character. The oxidation properties of the two macrocycles were studied through electron spin resonance spectroscopy and UV/Vis absorption spectrophotometry, which suggested the formation of a stable monoradical cation species on first oxidation followed by an aromatic dicationic species on subsequent oxidation. Both molecules have a nearly planar π‐conjugated backbone and show a strong tendency to aggregate in solution due to efficient stacking of the antiaromatic macrocycles. Transient absorption and two‐photon absorption (TPA) measurements in solution and aggregated states of the macrocycles revealed that aggregation resulted in large enhancement of TPA cross sections and increased excited‐state lifetimes, in accordance with the decrease in the antiaromatic character in the aggregated state. Abstract : Coming together : Antiaromatic macrocycles based on boron dipyrromethene (BODIPY) were synthesized through a one‐pot Knoevenagel condensation reaction (see figure). These macrocycles exhibit a strong tendency to aggregate in solution and display aggregation‐enhanced two‐photon absorption properties.